Storytelling of Myocardial Biopsy - Gaetano Thiene (Biology)
A biopsy involves the removal of a piece or an entire organ from a living patient. The former began with open heart surgery (surgical pathology) and the latter with the recipient heart in cardiac transplantation. Transvenous or transarterial catheterization is the current procedure to performed endomyocardial biopsy with bioptome from the ventricles. This manoeuvre was first carried out by Werner Forssmann through a urological catheter in 1929, which he introduced into his radial left vein until it reached the RV. Then, in London in 1974, Richardson invented a new technique with a catheter via the right femoral vein, which he applied with success in patients with multiple myocardial diseases, both inflammatory and non-inflammatory. Subsequently, a transjugular endomyocardial biopsy was accomplished by Margaret Billingham to monitor heart rejection during cardiac transplantation. In the beginning, only histology for a light microscope, and rarely during electron microscopy, was employed. With the advent of molecular techniques and the discovery of polymerase chain reaction (PCR), molecular investigation became part of the gold standard for diagnosis involving EMB: histology, immunohistochemistry and molecular investigation, the latter in search of a viral cause. Nowadays, EMB is frequently employed in infiltrative (amyloidosis) and storage diseases (e.g., hemochromatosis and Fabry diseases). Diagnosis of myocarditis is now possible through Magnetic Cardiac Resonance (MCR), in place of BEM histology, thanks to oedema. With the help of ECMO, it is possible to allow the heart to rest, supporting its recovery from ejection fraction even in fulminant myocarditis. Cardiac transplantation with the pathological study of the recipient heart offers the opportunity to discover and study new diseases, like restrictive cardiomyopathy and a non-compacted left ventricle.